2016
DOI: 10.2196/jmir.5794
|View full text |Cite
|
Sign up to set email alerts
|

Spanish-Language Consumer Health Information Technology Interventions: A Systematic Review

Abstract: BackgroundAs consumer health information technology (IT) becomes more thoroughly integrated into patient care, it is critical that these tools are appropriate for the diverse patient populations whom they are intended to serve. Cultural differences associated with ethnicity are one aspect of diversity that may play a role in user-technology interactions.ObjectiveOur aim was to evaluate the current scope of consumer health IT interventions targeted to the US Spanish-speaking Latino population and to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 120 publications
2
30
1
Order By: Relevance
“…Even among Latinos living in urban ethnic enclaves-where residents are more likely to share similar cultural norms and beliefs toward Western medicine-those speaking Spanish were less likely to have a regular source of health care (Alcala et al, 2016). To cope with linguistic barriers, different approaches to improve communication quality during health care visits have been developed (Chaet, Morshedi, Wells, Barnes, & Valdez, 2016;Genoff et al, 2016). For instance, a systematic review of cancer screening for patients with LEP found that patient navigation services improved rates of cancer screening by 7%-60% (Genoff et al, 2016).…”
mentioning
confidence: 99%
“…Even among Latinos living in urban ethnic enclaves-where residents are more likely to share similar cultural norms and beliefs toward Western medicine-those speaking Spanish were less likely to have a regular source of health care (Alcala et al, 2016). To cope with linguistic barriers, different approaches to improve communication quality during health care visits have been developed (Chaet, Morshedi, Wells, Barnes, & Valdez, 2016;Genoff et al, 2016). For instance, a systematic review of cancer screening for patients with LEP found that patient navigation services improved rates of cancer screening by 7%-60% (Genoff et al, 2016).…”
mentioning
confidence: 99%
“…Most of the training was related to teaching graduate STEM student trainees how to appeal to their audience. The workshops addressed audience limitations, abilities, biases, and the importance of researching the audience, segmenting, and tailoring the message to audiences (e.g., Chaet et al, ; Dirmaier et al, ; Takla et al, ; van Lieshout et al, ), as the responsibility for message delivery is on the scientist, not the audience.…”
Section: Discussionmentioning
confidence: 99%
“…Other issues, such as health literacy, affect message reception, as more than one‐third of U.S. Americans are below an intermediate level of health literacy—meaning, they may not be able to read and comprehend a prescription label without assistance (U.S. Department of Health & Human Services, ). Tailoring messages to audiences based on identity and characteristics, and reasons for accessing information (e.g., Chaet, Morshedi, Wells, Barnes, & Valdez, ; Dirmaier, Härter, & Weymann, ; Takla, Velasco, & Benzler, ; van Lieshout, Huntink, Koetsenruijter, & Wensing, ), often is more effective when appealing to an audience than a generic message (Young, Willis, Stemmle, & Rodgers, ). Studies about science communication training programs have echoed the need for these lessons to be included to achieve programmatic success.…”
Section: Making Effective Stem Science Communicatorsmentioning
confidence: 99%
“…Virtual agents have been developed to address a variety of health topics, including hospital discharge [4], childhood obesity [19], and mental health [18]. While there has been in an increase in consumer health information technology targeted at the Latino population, the majority of technology-enabled health promotion programs are aimed primarily at educated, health-literate individuals and are not tailored to diverse Latino subpopulations [7, 12]. Novel health communication technologies such as virtual humans that do not rely on advance reading or computer skills have the potential to break down health communication barriers and culturally adapt programs to diverse populations.…”
Section: Introductionmentioning
confidence: 99%